Diagnostic yield of genetic testing in epileptic encephalopathy in childhood. (25th March 2015) - Mercimek‐Mahmutoglu, Saadet; Patel, Jaina; Cordeiro, Dawn; Hewson, Stacy; Callen, David; Donner, Elizabeth J.; Hahn, Cecil D.; Kannu, Peter; Kobayashi, Jeff; Minassian, Berge A.; Moharir, Mahendranath; Siriwardena, Komudi; et al.
Summary Objective Epilepsy is a common neurologic disorder of childhood. To determine the genetic diagnostic yield in epileptic encephalopathy, we performed a retrospective cohort study in a single epilepsy genetics clinic. Methods We included all patients with intractable epilepsy, global developmental delay, and cognitive dysfunction seen between January 2012 and June 2014 in the Epilepsy Genetics Clinic. Electronic patient charts were reviewed for clinical features, neuroimaging, biochemical investigations, and molecular genetic investigations including targeted next‐generation sequencing of epileptic encephalopathy genes. Results Genetic causes were identified in 28% of the 110 patients: 7% had inherited metabolic disorders including pyridoxine dependent epilepsy caused by ALDH7A1 mutation, Menkes disease, pyridox(am)ine‐5‐phosphate oxidase deficiency, cobalamin G deficiency, methylenetetrahydrofolate reductase deficiency, glucose transporter 1 deficiency, glycine encephalopathy, and pyruvate dehydrogenase complex deficiency; 21% had other genetic causes including genetic syndromes, pathogenic copy number variants on array comparative genomic hybridization, and epileptic encephalopathy related to mutations in the SCN1A, SCN2A, SCN8A, KCNQ2, STXBP1, PCDH19, and SLC9A6 genes. Forty‐five percent of patients obtained a genetic diagnosis by targeted next‐generation sequencing epileptic encephalopathy panels. It is notable that 4.5% of patients had a treatable inherited metabolic disease. Significance To the best of our knowledge, this is the first study to combine inherited metabolic disorders and other genetic causes of epileptic encephalopathy. Targeted next‐generation sequencing panels increased the genetic diagnostic yield from <10% to >25% in patients with epileptic encephalopathy.